The Effect of Maximum Normal Impact Load, Absorbed Energy, and Contact Impulse, on the Impact Crater Volume/Depth of DLC Coating - Abdollah, Mohd Fadzli bin (jstage, 2011)
In this work, the influence of maximum normal impact load, absorbed energy, and contact impulse, on the impact crater volume/depth of a hydrogen-free diamond-like carbon coating (commonly known as DLC) has been studied. The tungsten high speed steel (SKH2) specimen discs were coated with DLC using the Physical Vapour Deposition (PVD) method. The 90o impact test was performed using a self-developed impact tester, where the DLC coated disc was impacted by a chromium molybdenum steel (SCM420) pin, at 400 impact cycles, under lubricated conditions. The results show that the most crucial factor, affecting the impact crater volume/depth of DLC coating under impact, is the maximum normal impact load.